Understanding Biology of Endometrial Cancer - 최동순 (The Graduate School, Ajou University, 2007)
Endometrial cancer (EC). is one of major malignancies in women, and it is known that unopposed excess estrogen is a major risk factor. Because carcinogenesis is believed to be a multistep process involving the accumulation of somatic and epigenetic mutations, it would be very helpful for diagnosis and treatment if there are either step-wised biomarkers or those distinguishing epithelial transformation from hyperplasia. In addition, carcinogenesis can be explained as a total outcome of cross-talks between stromal and transforming cells. Therefore, understanding biology of such communications will be beneficial in search of biomarkers, especially diagnosis and controlling tumorigenic growth of cancer cells. Interestingly, up-regulated expression of syndecan-1 has been reported in cases of hormone-related cancers such as osteosarcoma, breast, ovary, thyroid, and prostate cancers. However, there is not much known information about syndecan-1 for endometrial cancers. For these reasons, syndecan-1 was focused as a potential diagnostic and therapeutic marker by examining syndecan-1 expression in 109 tissue samples consisted of non-cancerous and cancerous tissues. Then, the biological meanings of syndecan-1 were sought in three endometrial cancer cell lines, HEC-1A, KLE, and AN3CA. As results, it was demonstrated that syndecan-1 was up-regulated in all cancer tissues while no immunoreaction was detected in non-cancerous tissues and that sydecan-1 acted as a critical membrane protein related with cellular viability and proliferation. Therefore, all of these indicate syndecan-1 as a good candidate for a biomarker. Secondly, attempts were made to elucidate what mediates invasion of endometrial cancer cells under hormonal influences, experienced often in clinical conditions. From previous studies, including ours, evidences suggest that HGF may be a good candidate for the cancer invasion. Therefore, a co-culture model system has been devised using normal stromal cells and endometrial cancer cell lines, HEC-1A and KLE. In order to mimic hormonal environments, culture condition was subdivided into five different ones, no treatment (No)., estrogen dominant (E2)., progesterone dominant (P4)., NK4, a HGF antagosnist, and E2 with NK4. Then, variable factors by paracrine interactions between stroma and cancer cells as well as the origin of HGF were investigated. The results show that HGF was originated from stromal cells and had effects on co-cultured cancer cells by enhancing invasion. This paracrine effect was more prominent in E2, but there was regression in the invasiveness under P4 conditions by which HGF was down-regulated. In addition, the enhanced invasion induced by HGF is appeared to be acquired from increased cellular attachment to substratum through increased expression and association of intergrin αvβ5 and FAK, respectively.
학위논문(박사)--아주대학교 일반대학원 :분자과학기술학과,2007.2
Keywords: endometrial cancer cell proliferation invasion syndecan-1 HGF cancer-stromal interaction